Analisis Supervisi Akademik Kepala Sekolah terhadap Perencanaan, Pelaksanaan, dan Evaluasi Pembelajaran Guru di SDN 101768 Tembung dari Perspektif Guru: The Boarding School System in Improving Moral Development at the Hasan Al-Massyath Nahdatul Wathon Gunung Sesang Terara Islamic Boarding School - Erika Juliani Purba; Dwi Sulistianing Warni; Fanny Tio Siahaan; Nur Hidayani Zahra; Rika Silalahi (Pendidikan Al-Gafari, 2026)
This study aims to analyze the implementation of the principal’s academic supervision and its influence on teachers’ lesson planning, instructional practices, and learning evaluation at SDN 101768 Tembung. The background of the study is rooted in the importance of academic supervision as a professional development process that ensures the quality of learning in elementary schools. This research employs a descriptive qualitative approach, with data collected through semi-structured interviews with teachers who provided comprehensive information regarding the principal’s supervisory practices and the school’s management of teaching and learning.The findings reveal that teachers are actively involved in lesson planning, including the preparation of teaching modules, learning media, and instructional plans, all of which are directly supervised by the principal. Academic supervision is carried out routinely every month through the review of instructional documents and the provision of feedback to teachers. This supervision has a positive impact, including increased motivation, pedagogical skills, and teacher discipline in classroom instruction.Furthermore, learning evaluation is conducted systematically through the development of assessment instruments that are monitored by both the principal and school supervisors, ensuring that the evaluation process is more objective and aligned with established standards. The main challenge identified is the scheduling of supervision activities due to the heavy workload of both the principal and teachers, although this constraint does not diminish the school’s commitment to continuous professional guidance.